Peramalan Tingkat Permintaan LPG PT. Pertamina (Persero) Di Elpiji Tandem - Joko Wijono; Ninny Siregar; M Banjarnahor (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
LPG that produced by PT. Pertamina (Persero) unit Pengolahan I Pangkalan Brandan cames from natural gas. LPG usually used by people for industry and home needs. Most of high-end community prefer to consume to fuel oil, outfil legible job decay (durable) bat need big investment(because the storages of LPG or LPG bottle is expensive). Most of LPG consumption for north sumatera consumer supplied by PT. Pertamina (Persero) Unit Pengolahan I Pangkalan Berandan. For maintaining LPG continuity, so demand forecasting is a neccessary for the future. Considering the decline of LPG production, which caused by natural trend linier gas reserver. To predict the demand in the demand in the future, it can count using and Exponential Smoothing forecasting method. Exponential Smoothing forecasting method that used is double Exponential Smoothing forecasting method and then parameter estimate to get the minimum (Mean Square Error).  From the calculation forecasting method, Double Exponential Smoothing forecassting method can give the minimum MSE price with one parameter 0,1 and for Depot Tandem UPMS I Medan in 2010 is79.740,414 kiloliter.Keywords : Eksponential Smoothing Methode , forecasting